Commercial foods for infants under the age of 36 months: An assessment of the availability and nutrient profile of ultra-processed foods - da Rocha, KF (2021)
Objective: Considering the negative impact of the consumption of ultra-processed foods on health, this study assessed the availability and nutritional profile of commercial ultra-processed foods for infants in Natal, Brazil. Design: A cross-sectional exploratory study. Setting: Foods targeted at children under the age of 36 months sold in retail establishments located in high and low-income areas of the one capital city of Brazil. Participants: 1,645 food products consisting of 95 different types of food were available. The foods were assessed according to the NOVA classification: minimally processed, processed, and ultra-processed. The nutritional content per 100g was assessed according to processing classification. Results: Half of foods founded were breast milk substitutes and cereal foods (31.6% and 26.3%, respectively). The foods were predominantly ultra-processed (79%) and only 4.2% were minimally processed, with similar proportions of ultra-processed foods being found in both high and low-income areas. After excluding breast milk substitutes and follow-up formulas, all cereals, food supplements and some of the fruit or vegetable purees were ultra-processed, higher in energy density, fat, carbohydrate and protein, and low in fiber (P<0.05). Conclusions: The findings reveal that ultra-processed foods for infants are widely available in Brazil, reaffirming the need to strengthen the regulation of foods for infants and young children by introducing complementary measures designed to promote the production and marketing of foods manufactured using lower levels of processing.